Thermodynamic and functional characterization of the periplasmic triheme cytochrome PpcA from Geobacter metallireducens - Fernandes, Tomás M. (2022)
SFRH/BPD/114848/2016. PTDC/BBB-BQB/3554/2014. POCI-01-0145-FEDER-007728 National NMR Network (PTNMR) and are supported by Infrastructure Project No022161.